Formulation and Sensory Reception of Steamed Brownies with Avocado (Persea americana) Seeds as Additive - Adisty, Amanda Dwi Oktavia; Rahayu, Wahidah Mahanani; Juwitaningtyas, Titisari (Universitas Ahmad Dahlan, 2020)
Avocado (Persea americana) is a fruit part of the Lauraceae family, which can be widely found in tropical and subtropical regions. With an annual harvest of more than 300,000 tons in Indonesia and only flesh as edible part, avocado has large byproducts such as skin and seed. The later contains 23% of starch and fat, which can be utilized as an alternative source of starch. This study aimed to examine consumer preference for steamed brownies with avocado seed as additive. Preference was measured using a hedonic test on 55 untrained panelists at a measurable scale of 1-7. Results showed that brownies made by 90 g shredded avocado seed and 80 g wheat flour had the highest hedonic score for color, appearance, texture, aroma, and flavor of 4.4, 4.2, 4.1, 3.75, and 3.7, respectively. These results indicated the possibility to develop a better formula to produce steamed brownies with avocado seed preferable by consumers.